If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6 + -1x) = 24 (6 * -1 + -1x * -1) = 24 (-6 + 1x) = 24 Solving -6 + 1x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 1x = 24 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 24 + 6 1x = 24 + 6 Combine like terms: 24 + 6 = 30 1x = 30 Divide each side by '1'. x = 30 Simplifying x = 30
| 6c-5=5.0(6+4c) | | 11(k-1)=7(k-7) | | 6x^2+11x=8 | | 6c-5=2(6+4c) | | 16=-3(2x+1)+7x | | 20x^4-21x^2+1=0 | | 2x^2+16x=5x+21 | | In(x^4)-In(x^2y)+In(y^2)=0 | | e-29.3=14.5 | | 5x=30*3x | | 2x-14=2x-17 | | p-13.7=47.8 | | x*x=3x+10 | | 5x+x-2=5x+6 | | 15y+3(2-y)=-24 | | (3k-4)(3k+4)= | | 2*.5+2Y=15 | | 7+7-3+70+1= | | e-4.7=2.9 | | 2+.5+2Y=15 | | 0.5(p+3)=3(0.1+0.6p) | | -2k+5k-9+2k= | | 4x+10[2x+2]-15= | | 75=15k+6 | | 9x^3-9x^2-x+1=0 | | 10+3[x+5]-x= | | b-339=-77 | | 20-7x=4(2x-6) | | 6x-1=-4 | | 9x^2-18x-91=0 | | 3x^2+28x-9=0 | | -6x+4=-10x+24 |